Impacat of climate stress on selected marine biota - Mary Agnus, K A (Academy of Climate Change Education and Research, 2018)
Resilience capacity based on response to short term (6 hrs to 4 days) exposures to 5 to 45 ppt salinities and temperature (30 to 42 o C) followed by revival indicated that the clam Villorita cyprinoides (adult and juvenile) and the teleost fish Etroplus suratensis (pearl spot) had high resilience to sudden exposure to extreme temperatures (40-42 o C). Adult green mussel, Perna viridis (adult green mussel) was found to be moderately vulnerable to the high temperatures. Trachinotus blochii (silver pompano), post larvae of the shrimp Penaeus monodon and seed of Perna viridis were found to be vulnerable to high temperature (40 to 42 o C). From the observations, only three species, V. cyprinoides, E. suratensis and P.monodon were found to be adaptive and resilient to the low-medium salinities, but vulnerable to the extreme saline conditions. P. viridis (Adult) and T. blochii had higher mortality in both low-saline (5-20 ppt) and hyper-saline (40-45 ppt) conditions. Phytoplankton Isochrysis galbana could tolerate upto 34 o C and were capable of multiplication of cells in higher temeprature. However, they were vulnerable to sudden exposure to 36 o C. In the experiments on varied pH, swimming was found to be disoriented in juvenile clown fish, Amphiprion percula and the zooplankton, Daphnia salina when pH ranged from 6.40 to 6.70. In pH 6.8 and above they were found to be active. Heavy precipitation related to extreme events can be tolerated only by juvenile pearl spot, black clam and post larvae of tiger shrimp. Juvenile silver pompano, post larvae of tiger shrimp and, seed and adult mussels are vulnerable to increase in SST and drought like situations. Based on the behavioural response and survival of the resources, management advisories for reducing crop loss can be developed for mariculture which would increase the preparedness of the farmers to face climate change. Fish farmers are advised to avoid stocking fish seed during summer months. Farmers should try to reduce the water temperature in the farm by providing provisions for water circulation and shades. Mussel farmers are advised to stock the seed only after the farm salinity stabilizes at 25 ppt. They should harvest the mussel stock in the farm within 12 hrs when the salinity drops below 25 ppt or if the salinity increases above 35 ppt and also when the sea surface temperature (SST) in the farm increases above 34 o C. In marine hatcheries, phytoplankton crashes can be expected in outdoor tanks when the salinity increases above 34 o C, hence hatchery operators are advised to take necessary precaution to prevent sudden collapse during summer. In estuarine areas, it is advisable to plant more mangroves which can protect natural resources during peak summer period. Reduced water flow and stagnation of water should be rectified to ensure continuous water flow which would otherwise exacerbate impacts of extreme events related to climate change.